FILOSOFI LAUT MALUKU DALAM PARADIGMA BLUE ACCOUNTING - Bakri, Muh. Ziaul Haq; Rabiyah, Ulfa; Amahoru, Nur Hikmah Helida; Paledung, Marannu (POLITEKNIK LP3I JAKARTA, 2026)
The sea, as the lifeblood of Indonesian coastal communities, particularly in the Maluku Islands, plays a central role in economic, social, and cultural aspects. Although the blue accounting paradigm offers a solution for integrating ecological and social dimensions in marine accounting reporting, many practices still focus on a technocratic approach that tends to ignore local values. This study aims to develop a blue accounting paradigm based on the local wisdom of the Maluku community, by exploring customary principles such as Sasi and Pela Gandong, which focus on ecological balance and sustainability. Through a reflective-philosophical approach, this study analyzes the ontological, epistemological, and axiological dimensions that shape the Maluku community's perspective on the sea. The findings indicate that the sea is not only viewed as an economic resource, but as a living entity containing moral and spiritual values. Therefore, blue accounting needs to accommodate these values ​​in the reporting system to produce fairer and more sustainable accountability. This study also suggests the integration of local wisdom within national and international policy frameworks, as well as the importance of developing customary-based indicators to strengthen the sustainability of marine ecosystems.